The Effect of Organizational Support Perceived by Nurses on Their Leadership Styles and Problem Solving Skills - Şahin Koç; Serap Altuntaş (Association of Nurse Managers, 2018)
INTRODUCTION: Nurses need to be supported by the institution they are working with so that they can solve the problems they face and lead effectively. This study was conducted as descriptive, cross -sectional and correlation research with the aim of determining the effect of organizational support perceived by nurses on their leadership styles and problem solving skills. METHODS: The study was carried out between the dates of March 2014 and October 2015. The study data were collected from 460 nurses who agreed to participate in the study, working in four hospitals operating in a provincial center. The data were collected using a personal information form, the Perceived Organizational Support Scale, the Multi-factor Leadership Scale and the Problem Solving Inventory. The collected data were evaluated with statistical package programs in computer environment. RESULTS: It was determined that nurses perceive the most organizational support for justice (M=28.57+-8.79), choose the transformational leadership style (M=3.72+-0.54) and prefer an impetuous approach (M=30.29+-4.85) when they are solving their problems. There are significant relationships between the dimensions of organizational support perceived by nurses and their leadership styles (p<0.05), and there is a strong, significant relationship between their leadership style and problem solving skills (p<0.001). It was found that perceived organizational support has an effect on the leadership style of nurses, and that their leadership styles have a profound effect on their problem solving approaches. DISCUSSION AND CONCLUSION: The study concluded that perceived organizational support affects the leadership styles of nurses, and the leadership styles affect their problem solving skills.